2020
DOI: 10.1177/1363461520903122
|View full text |Cite
|
Sign up to set email alerts
|

Sleep difficulties among South Sudanese former refugees settled in Australia

Abstract: This quantitative study investigated self-reported sleep, mental health and trauma related nocturnal behaviours among South Sudanese Australians (SSA), examined sex differences in their responses, and sought to determine risk factors for insomnia in this population. Comparisons were also made to a general Australian (AUS) sample of 1,512 respondents, obtained in a previously published study using the same questions regarding sleep difficulties. Self-reports of sleep difficulties, psychological distress (Kessle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Measured on a scale of 0 to 7 Mean score Validated in a multisite international study covering Australia, Brazil, India, Thailand, UK, USA, and Zimbabwe [ 29 ]. It has also previously been validated in Rhino settlement ( https://www.elrha.org/project/improving-the-mental-health-of-refugee-men-through-guided-self-help-a-scalable-intervention-for-a-critical-link-in-humanitarian-programming/ , Paper forthcoming) K10 [ 24 ] Ten-item scale on non-specific psychological distress, scored on a scale of 1 to 5 Mean score Validated amongst South Sudanese refugees [ 41 ], and in Rhino settlement ( https://www.elrha.org/project/improving-the-mental-health-of-refugee-men-through-guided-self-help-a-scalable-intervention-for-a-critical-link-in-humanitarian-programming/ ) PHQ-9 [ 30 ] Nine-item questionnaire on prevalence of depressive symptoms assessed on a scale of 0 to 3 Mean score Validated amongst South Sudanese refugees and in northern Uganda [ 42 ] HSCL-A [ 31 ] Ten-item questionnaire on prevalence of anxiety symptoms, assessed on a scale of 1 to 4 Mean score Previously validated in multiple low and middle income settings, including Uganda [ 43 ] PCL-6 [ 44 ] Six-item measure on prevalence of PTSD, assessed on a scale of 1 to 5 Mean score Good psychometric properties amongst female South Sudanese refugees in Rhino settlement [ 45 ] WHODAS 2.0 [ 33 ] Twelve-item measure of health and disability, which covers the domains of cognition, mobility, self-care, getting along, life activities and participation in the last 30 days. It is assessed on a scale of 1 to 4 Mean score Good psychometric properties amongst female South Sudanese refugees in Rhino settlement [ 45 ] …”
Section: Interventionsmentioning
confidence: 99%
“…Measured on a scale of 0 to 7 Mean score Validated in a multisite international study covering Australia, Brazil, India, Thailand, UK, USA, and Zimbabwe [ 29 ]. It has also previously been validated in Rhino settlement ( https://www.elrha.org/project/improving-the-mental-health-of-refugee-men-through-guided-self-help-a-scalable-intervention-for-a-critical-link-in-humanitarian-programming/ , Paper forthcoming) K10 [ 24 ] Ten-item scale on non-specific psychological distress, scored on a scale of 1 to 5 Mean score Validated amongst South Sudanese refugees [ 41 ], and in Rhino settlement ( https://www.elrha.org/project/improving-the-mental-health-of-refugee-men-through-guided-self-help-a-scalable-intervention-for-a-critical-link-in-humanitarian-programming/ ) PHQ-9 [ 30 ] Nine-item questionnaire on prevalence of depressive symptoms assessed on a scale of 0 to 3 Mean score Validated amongst South Sudanese refugees and in northern Uganda [ 42 ] HSCL-A [ 31 ] Ten-item questionnaire on prevalence of anxiety symptoms, assessed on a scale of 1 to 4 Mean score Previously validated in multiple low and middle income settings, including Uganda [ 43 ] PCL-6 [ 44 ] Six-item measure on prevalence of PTSD, assessed on a scale of 1 to 5 Mean score Good psychometric properties amongst female South Sudanese refugees in Rhino settlement [ 45 ] WHODAS 2.0 [ 33 ] Twelve-item measure of health and disability, which covers the domains of cognition, mobility, self-care, getting along, life activities and participation in the last 30 days. It is assessed on a scale of 1 to 4 Mean score Good psychometric properties amongst female South Sudanese refugees in Rhino settlement [ 45 ] …”
Section: Interventionsmentioning
confidence: 99%
“…However, studies on insomnia in internally displaced persons are limited, especially among the adolescent group, which constitutes over 60% of all IDPs in north-eastern Nigeria (IOM 2021). The few existing studies from Russia, North Korea, and Australia have reported a high prevalence in displaced populations, with incidence of 44% (Basishvili et al 2012), 38% , and 32% (Bruck et al 2020). Therefore, there is a clear need to study insomnia as an independent disorder within internally displaced adolescents (IDAs) in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of insomnia or sleep disturbances appears to be considerably higher for refugees than among the general population (Bruck et al, 2021;Lee et al, 2016;Molsa et al, 2014). Although in the general population, women are more likely to report insomnia than men (Suh et al, 2018), this does not appear to be the case for refugees (Bruck et al, 2021;Mangrio et al, 2020). Prevalence estimates may also vary by migrant group, settlement country and resettlement time, as well as by definition of, and way of measuring, insomnia.…”
mentioning
confidence: 96%
“…Pre-migration trauma is strongly associated with insomnia among refugees (Basishvili et al , 2012; Bruck et al , 2021). Insomnia is, in turn, linked to higher levels of mental health problems, chronic pain and poorer self-perceived health (Al-Smadi et al , 2019; Bruck et al , 2021; Lies et al , 2019, 2021; Mangrio et al , 2020; Park et al , 2019). Furthermore, it is also a common symptom of post-traumatic stress disorder (PTSD) (Sandahl et al , 2017).…”
mentioning
confidence: 99%